Seasonal evolution of an ice‐shelf influenced fast‐ice regime, derived from an autonomous thermistor chain. Issue 3 (19th March 2015) - Hoppmann, M.; Nicolaus, M.; Hunkeler, P. A.; Heil, P.; Behrens, L.‐K.; König‐Langlo, G.; Gerdes, R.
Abstract Ice shelves strongly interact with coastal Antarctic sea ice and the associated ecosystem by creating conditions favorable to the formation of a sub‐ice platelet layer. The close investigation of this phenomenon and its seasonal evolution remains a challenge due to logistical constraints and a lack of suitable methodology. In this study, we characterize the seasonal cycle of Antarctic fast ice adjacent to the Ekström Ice Shelf in the eastern Weddell Sea. We used a thermistor chain with the additional ability to record the temperature response induced by cyclic heating of resistors embedded in the chain. Vertical sea‐ice temperature and heating profiles obtained daily between November 2012 and February 2014 were analyzed to determine sea‐ice and snow evolution, and to calculate the basal energy budget. The residual heat flux translated into an ice‐volume fraction in the platelet layer of 0.18 ± 0.09, which we reproduced by a independent model simulation and agrees with earlier results. Manual drillings revealed an average annual platelet‐layer thickness increase of at least 4 m, and an annual maximum thickness of 10 m beneath second‐year sea ice. The oceanic contribution dominated the total sea‐ice production during the study, effectively accounting for up to 70% of second‐year sea‐ice growth. In summer, an oceanic heat flux of 21 W m−2 led to a partial thinning of the platelet layer. Our results further show that the active heating method, in contrast to the acoustic sounding approach, is well suited to derive the fast‐ice mass balance in regions influenced by ocean/ice‐shelf interaction, as it allows subdiurnal monitoring of the platelet‐layer thickness.